2005
DOI: 10.1080/14764170500430234
|View full text |Cite
|
Sign up to set email alerts
|

Cellulite: Is there a role for injectables?

Abstract: Until further studies are performed, patients considering mesotherapy for cellulite must be aware that the substances currently being injected to treat this cosmetically disturbing, but medically benign, condition have not been thoroughly evaluated for safety or efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 86 publications
0
32
0
2
Order By: Relevance
“…[47][48][49] Some studies have been revised regarding the role of mesotherapy in gynoid lipodystrophy 50 and others regarding the role of mesotherapy lipolysis. 3,6,51 These revisions offer the conclusion that, theoretically, a subcutaneous injection of specified products can function, but they lack indexed scientific publications on which to base this technique.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[47][48][49] Some studies have been revised regarding the role of mesotherapy in gynoid lipodystrophy 50 and others regarding the role of mesotherapy lipolysis. 3,6,51 These revisions offer the conclusion that, theoretically, a subcutaneous injection of specified products can function, but they lack indexed scientific publications on which to base this technique.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior to these findings, the only clinically confirmed treatment of NASH was weight reduction (Moschen and Tilg, 2008). Fat dissolving local injections have two therapeutic effects; First, the injected reagents are toxic to adipose and other associated cells, causing permanent removal of fat tissue; second, the injections have been associated with a temporary decrease in the fat stores, resulting in smaller fat cells (Rotunda et al, 2005). The results of this study showed that the effects of PTX on adipocyte cells differed according to the PTX concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Mesotherapy, originally introduced in Europe, is a minimally invasive technique that consists of the intra-or subcutaneous injection of variable mixtures of natural plant extracts, homeopathic agents, pharmaceuticals, vitamins, and other bioactive substances (Accessed February 2nd, 2009). The use of mesotherapy in cosmetic medicine, to reduce and contour subcutaneous fat, is gaining popularity (Rotunda et al, 2005;Doerr, 2007), however, the safety and efficacy of this treatment has not been scientifically validated.…”
Section: Introductionmentioning
confidence: 99%
“…LPL is located on endothelial walls of capillaries and is responsible for serum chylomicron (from dietary lipids) and very low-density lipoprotein breakdown. Lipolysis may also be induced by medication binding to specific adrenergic receptors (α or β) located on adipocyte membranes [15][16][17][18]. A novel medication currently being developed by Lithera, Inc. (San Diego, CA) is termed "LIPO-102" and its use as an injectable fat reducer is called "pharmaceutical lipoplasty."…”
Section: Clarification Of Terms and History Lipolysis Injection Lipomentioning
confidence: 99%